Transmissionales in Causa Possessionis Resinar contra Liberam Regiamque Civitatem Cibiniensem. A unique documentary source for learning about the rights and customs of the Romanians (Ius Valachicum) from Rășinari (Transylvania) in the 18th century - Vizauer, Victor V. (Balcanica Posnaniensia. Acta et studia, 2025)
Through this article, I aim to bring to the attention of those interested an intriguing and significant document, both for the local history of the commune of Rășinari (in Sibiu County, Romania) and for the broader history of Transylvania in the 18th century. Entitled Transmissionales in causa possessionis Resinar contra Liberam Regiamque Civitatem Cibiniensem, this unpublished volume of 1,318 pages comprises the documents related to the lawsuit filed by the Romanians (Vlachs) of the village of Rășinari against the Magistrate (Council) of the city of Sibiu, a legal dispute that took place between 1735 and 1784. The reasons behind this lawsuit, initiated by the people of Rășinari, were the repeated violations of their ancient rights by the Saxon mayors of Sibiu and the abuses committed by them. The records of this lengthy trial, which ultimately concluded in favor of the inhabitants of Rășinari, reveal valuable information regarding, among other things, the customary law of the Romanians (Ius Valachicum) living in Rășinari and in other neighboring localities throughout the 18th century.